Biomechanical analysis in freestyle snowboarding: application of a full-body inertial measurement system and a bilateral insole measurement system - Krüger, A.; Edelmann-Nusser, J. (Sports Technology, 2009)
Several investigations show that 5-28% of all snowboarding injuries relate to the ankle joint complex. To reduce the risk of ankle injuries, the development of enhanced snowboard equipment is considered. Therefore, it is essential to understand the biomechanics in snowboarding. Scientific studies investigating the ankle joint complex in freestyle snowboarding, including inrun, flight phase, and landing, are so far not available. An auspicious method to determine relevant kinematical and kinetic parameters is based on the utilization of an inertial measurement suit in combination with a bilateral insole measurement system. This pilot study aims at the application of these two systems in freestyle snowboarding for data collection in a real snowboarding environment. The accuracy of the used measurement systems is assessed. The insole measurement system shows a root mean square error of 28% (± 6.6%) in reference to a force plate. A maximum mean deviation of 4.81 (± 0.3°) is found in the inertial measurement system compared to an optical video-based system. The on-snow data collection reveals valuable information and provides a better understanding of the biomechanics in freestyle snowboarding. Ranges of movement of the ankle joint complex and forces essential to perform snowboarding maneuvers are measured. In addition, combinations of joint angles and landing forces occurring during the landing phase of an aerial maneuver are found that have the potential to cause injuries. Critical values of 25° dorsiflexion and 81 external rotation in combination with a normal force of 3020 N are measured at the back leg.